Fonem Segmental Bahasa Kanum Barkari - Siti Masitha Iribaram (Kantor Bahasa Provinsi Maluku Utara, 2015)
The purpose of this research is to describe the segmental phonemes of Kanum Barkari language. This language is located at territorial border between Indonesia and Papua New Guini. Kanum Barkari language is one of vernacular language spoken by peoplein Kondo village at Merauke Regency, Papua. This research uses descriptive method by using three stages; collecting, analyzing, and presenting data. Data analysis has been done after the collected data is classified. The analysis uses a distributional method. The results show that Kanum Barkari language has 16 consonant phonemes,namely, /p/, /b/, /t/, /d/, /j/, /k/, /g/, /m/, /n/, /ŋ/, /l/, /s/, /r/, /h/, /w/, /y/ and 6 vowel phonemes, /a/, /i/, /u/, /e/, /є/, dan /o/.